Effects of Artificial Intelligence and Virtual Reality in Martial Arts Sports on Students’ Physical and Mental Health - JingGang Li; XiaoShuang Wang; LiJun Wang; Hyoungkil Kang (International Transactions on Electrical Energy Systems)
As a treasure left over from Chinese traditional culture, martial arts have a long history and lasts for a long time. With the country’s promotion and support of martial arts culture, martial arts have also attracted more and more people’s attention. In order to carry forward the martial arts culture, the combination of martial arts and sports has formed a set of martial arts sports suitable for today’s students, such as martial arts aerobics. It is used as a class exercise for students, and basically, every student in the school has learned it and practiced it often. However, with the development of the times, it is difficult for today’s students to arouse students’ enthusiasm for martial arts sports for traditional martial arts sports. Artificial intelligence technology and virtual reality, as products of today’s digital age, attract the attention and use of students with their unique features. This also means that the reform of martial arts sports based on artificial intelligence and virtual reality technology is imperative in order to make more students regain their enthusiasm for martial arts sports. However, the specific impact of artificial intelligence and virtual reality on the physical and mental development of students in martial arts sports is a problem to be confirmed by research. Through in-depth research on artificial intelligence and virtual reality technology, this paper shows that artificial intelligence and virtual reality martial arts sports can increase the lung capacity of boys by about 14% and girls by 16%; the effect on physical fitness can increase the lower body strength of boys by 3% and the flexibility of girls by 30%; as for the impact on mental health, it can be concluded that the emotional and cognitive dimensions of boys and girls have increased by about 19% compared with the previous values.